Talmon-Heller, Daniella, Sacred Place and Sacred Time in the Medieval Islamic Middle East. A Historical Perspective, Edinburgh University Press, Edinburgh 2020, 288 p. - Patriarca, Giovanni (Anaquel de Estudios Árabes, 2022)
Reseña de la obra de Talmon-Heller, Daniella, Sacred Place and Sacred Time in the Medieval Islamic Middle East. A Historical Perspective, Edinburgh University Press, Edinburgh 2020, 288 p.